(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT This article explores the importance of stylistic analysis in modernist poetry. It is written about improving stylistic analysis of modernist poetry in the late 19th and early 20th centuries. During writing this article it is informed text selection, literary framework, stylistic features analysis, thematic exploration, imagery and sound devices and made some discussion about reflection of modern experience, language as a tool for meaning, the role of imagery. In this article, is used some researchers’ works.